Digital economy-driven export sophistication: mechanisms of market integration and human capital restructuring - Jie Liu; Yexuan Guan; Mengjie Guan; Jingya Yu (Digital Economy and Sustainable Development)
Abstract Promoting the transformation of the foreign trade system and export upgrading has become necessary to promote high-quality economic development and build a new pattern of opening up to the outside world. This study constructs a theoretical framework of export upgrading driven by digital economy and empirically tests the export upgrading effect of the digital economy through rigorous econometric analysis. It is found that the digital economy has a significant positive impact on export upgrading, and the results are robust after both robustness test and endogeneity test; the export upgrading effect of digital economy will weaken with the development of digital economy; the digital economy policy represented by "broadband China" has produced a significant export upgrading effect; the digital economy can drive export upgrading by reducing market segmentation and promoting market integration; the impact of the digital economy on export upgrading has a double-threshold effect with human capital as the threshold variable, which shows that when human capital is in the second threshold range, it is more closely integrated with the digital economy and can better exploit the export upgrading effect of the digital economy; the heterogeneity analysis reveals that the export upgrading effect of digital economy is more significant in central and western regions than in the eastern regions, and the export upgrading effect of digital economy is more significant in regions with higher degree of industrial structure optimization. The study's findings provide valuable references for decision making to break the "big-in, big-out" trade pattern and realize the transformation of the foreign trade system.